Métodos analíticos alternativos para avaliação da qualidade de forrageiras utilizadas na nutrição animal - Carapelli, Rodolfo (Universidade Federal de São Carlos, 2007)
Alternative methods were developed for some determinations performed in routine by animal nutrition laboratories, in order to increase laboratory efficiency and reduce costs maintaining analytical quality. In the first step, a multicomutation point to point potentiometric titration system to total acid in silage extracts with the use of a PVC (tridodecilamine) membrane electrode is described. The multicommutation developed system employed three solenoid valves for solution management and a peristaltic pump for the fluid propulsion. The time and sequence of switching valves, the velocity of peristaltic pump and the data acquisition were performed through a developed program in the Labview® platform using a computer with an electronic interface. Silage samples of Brachiaria grass, sugar cane and corn were analyzed by the proposed system in order to method validation. The results indicated agreement in order of 95% of confidence when were compared with the ones obtained by gas chromatography (acetic, propyonic and butyric acids), and liquid (lactic acid), and by bath titration. In a second step, an alternative method for determination of neutral detergent fiber in forage samples was proposed, with the use of the nylon bag technology to samples storage, and a semi-pressure system heating by microwave radiation. This analyze consists of a cellular inner components solubilization in neutral detergent solution, remaining the neutral detergent fiber, basically formed by cellulose, hemicelluloses, lignin, lignin protein and silica, gravimetrically determined after oven drying. The method was validated from samples analysis supplied by the Ensaio de Proficiência de Laboratórios de Nutrição Animal , coordinate by Embrapa Cattle-Southeast. High correlation was obtained among the results obtained with the proposed method and furnace by the program, therefore its employment could be recommended.
Altenative analytical methods to quality evaluation of forages used in animal nutrition
Keywords: Multicomutação; Eletroanalítica; Fibra detergente neutro; Microondas; CIENCIAS EXATAS E DA TERRA::QUIMICA